Double trouble: Detection of rickettsial DNA in a tick removed from an otoacariasis patient - K. O. Bandaranayaka; S. A. M. Kularatne; R. P. V. J. Rajapakse; U. B. Abeysundara; R. M. M. A. Rajapaksha; R. S. Rajakaruna (Sri Lankan Journal of Infectious Diseases, 2021)
NA